2022
DOI: 10.3390/jcm11133626
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Post-Operative Relationship between Radiological Measures and Clinical Outcomes in Women with Hallux Valgus

Abstract: The surgical correction of a hallux valgus (HV) deformity improves radiological parameters and clinical outcomes. However, it is not known how these improvements are related between themselves. In this retrospective study, 73 women were assessed preoperatively and 60 months after HV surgical correction. Several radiological parameters were measured: the hallux valgus angle (HVA), I–II intermetatarsal angle (IMA) and sesamoid position. The functional outcomes were assessed using the American Orthopaedic Foot an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…With the use of a MIIND, Biz et al [ 13 ] found an improvement in AOFAS score from 57.9 preoperatively to 90.5 after a mean of 96 months postoperatively. Motta et al [ 20 ] found a pre-to-post difference of 54 points 6 years after the operation (from 35 to 90 points). Castellini et al [ 9 ] reported pre- to postoperative changes in AOFAS scores from 47.3 to 87.0 points, respectively, 2 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With the use of a MIIND, Biz et al [ 13 ] found an improvement in AOFAS score from 57.9 preoperatively to 90.5 after a mean of 96 months postoperatively. Motta et al [ 20 ] found a pre-to-post difference of 54 points 6 years after the operation (from 35 to 90 points). Castellini et al [ 9 ] reported pre- to postoperative changes in AOFAS scores from 47.3 to 87.0 points, respectively, 2 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We did not radiologically assess at any time point possible changes. However, we aimed to study only clinical score changes, and several publications have shown no significant correlation between radiological and clinical findings in patients with HV [ 16 , 20 , 21 , 36 ]. Moreover, some authors have reported that predictors of patient satisfaction include subjective outcomes, such as those assessed by the AOFAS score and the Short Form 36 composite quality of life scale, rather than objective radiological outcomes [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations